Africa : the future of management education. volume 2 - Thomas, Howard; Lee, Michelle (Associate Professor of Marketing); Thomas, Lynne; Wilson, Alexander, active 2017 (Emerald Publishing Limited, 2017)
Africa is commonly perceived as a global growth region and a continent on the move, with a huge demand for managerial skills to ensure sustainable economic growth. In order to gain a comprehensive understanding of the challenges to management education development in Africa, it is important to understand the diverse cultures, histories and contexts underlying the 54 member states. With this is mind, this book explores the future of management education, considering the differing scenarios for change and the practical realities of developing management education in VUCA (volatile, uncertain, complex and ambiguous) environments.This book, written with strong support from the EFMD (European Foundation for Management Development) and the GMAC (Graduate Management Admission Council), aimed at understanding and examining the challenges of developing management education across Africa. The authors, through a fine-tuned, face-to-face interview process, explore the perspectives and interactions between management educators and other business and government stakeholders as they look to the future of management education in Africa.